Prevalence and risk factors of neurological impairment among children aged 6-9 years: from population based cross sectional study in western Kenya - Kawakatsu Yoshito; Kaneko Satoshi; Karama Mohamed; Honda Sumihisa (BMC, 2012)
Abstract Background The burden of disability is more severe among children in low income countries. Moreover, the number of children with disabilities (CWDs) in sub-Saharan Africa is predicted to increase with reduction in child mortality. Although the issue on CWDs is important in sub-Saharan Africa, there are few researches on risk factors of disabilities. The purpose of this study was to evaluate the risk factors of neurological impairment (NI) among children in western Kenya. Methods The present study was conducted in Mbita district (which has high HIV infectious prevalence), Kenya from April 2009 to December 2010. The study consisted of two phases. In phase 1, the Ten Question Questionnaire (TQQ) was administered to all 6362 caregivers of children aged 6-9 years. In phase two, all 413 children with TQQ positive and a similar number of controls (n=420) which were randomly selected from children with TQQ negative were examined for physical and cognitive status. In addition, a structured questionnaire was also conducted to their caregivers. Results The prevalence was estimated to be 29/1000. Among the types of impairments, cognitive impairment was the most common (24/1000), followed by physical impairment (5/1000). In multivariate analysis, having more than five children [adjusted odds ratio (AOR): 2.85; 95%IC: 1.25 - 6.49; p=0.013], maternal age older than 35 years old [AOR: 2.31; 95%IC: 1.05 - 5.07; p=0.036] were significant factors associated with NI. In addition, monthly income under 3000 ksh [AOR: 2.79; 95%IC: 1.28 - 6.08; p=0.010] and no maternal tetanus shot during antenatal care [AOR: 5.17; 95%IC: 1.56 - 17.14; p=0.007] were also significantly related with having moderate/severe neurological impairment. Conclusion It was indicated that increasing coverage of antenatal care including maternal tetanus shot and education of how to take care of neonatal children to prevent neurological impairment are important.